Progressive resistance training in patients with shoulder impingement syndrome: literature review - A. Jones; R. Trajano Jorge; M. Cardoso de Souza; I. Lombardi Júnior; J. Natour (PAGEPress Publications, 2011)
The upper limbs perform diverse functions related to activities of daily living and labor activities. This occurs due to the considerable range of motion of the shoulder (1). The shoulder is a complex of muscles, bone articulations and functional articulations that allow greater mobility than in any other joint in the human body. However, this mobility is achieved at the cost of structural stability (2). Shoulder conditions are among the most common peripheral complications (3, 4). Activities that employ the arms or hands are known to increase the risk of the development of shoulder pain (3)....